PRE-CLINICAL STUDY OF EXPECTORANT PROPERTIES OF “AMBROL” TABLETS - Abdijalilova, Z.Kh. (International Journal of Psychosocial Rehabilitation, 2020)
Ambrol is used in conditions where there is a lot of viscous secretion or mucus in the airways. Ambrol is intended for the treatment of acute and chronic infectious respiratory diseases associated with impaired secretion. It stimulates the formation of low viscosity tracheobronchial secretion due to a change in the structure of sputum mucopolysaccharides and increases the secretion of glycoproteins (mucokinetic effect). It stimulates the motor activity of cilia of the ciliated epithelium and improves mucociliary transport, increases the synthesis, secretion of surfactant and blocks its decay. We aimed to study the bioequivalence of the drug “Ambrol”, to study acute toxicity and specific activity.